Multiplex Polymerase Chain Reaction Reveals Unique Trends in Pathogen and Parasitoid Infestations of Alfalfa Leafcutting Brood Cells. Issue 4 (4th August 2022) - Clements, Justin; Haylett, Maggie; Nelson, Brenda; Shumate, Silas; Young, Nicole; Bradford, Benjamin; Walsh, Doug; Lamour, Kurt
Abstract: The alfalfa leafcutting bee Megachile rotundata Fabricius (HYMENOPTERA: Megachilidae) is an important pollinator for multiple agricultural seed commodities in the United States. M. rotundata is a solitary cavity nesting bee that forms brood nests where its larvae can develop. During the developmental stages of growth, brood can be preyed upon by multiple different fungal pathogens and insect predators and parasitoids, resulting in the loss of the developing larvae. Larval loss is a major concern for alfalfa ( Medicago sativa L.) seed producers because they rely on pollination services provided by M. rotundata . Reduced pollination rates result in lower yields and increased production costs. In the present study, we examined the taxonomic composition of organisms found within M. rotundata brood cells using a multiplex PCR assay which was developed for the detection of bacterial, fungal, and invertebrate pests and pathogens of M. rotundata larvae. Known pests of M. rotundata were detected, including members of the fungal genus Ascosphaera, the causative agent of chalkbrood. The presence of multiple Ascosphaera species in a single brood cell was observed, with potential implications for chalkbrood disease management. The multiplex assay also identified DNA from more than 2, 400 total species, including multiple predators and pathogenetic species not previously documented in association with M. rotundata brood cells.